Analysis Of The Determinants Of Small And Medium Industry (SMI) Development On Labor Absorption In Medan City - Rizky Muhammad Husein; Rahmad Sembiring; Lia Nazliana Nasution (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is analyze the determinants of Small and Medium Industry (SMI) development on labor absorption in Medan City. The dependent variable in this study is labor, while the independent variables include economic growth, wages, investment, production, productivity, the open unemployment rate, and the Human Development Index (HDI). This study uses secondary data obtained from the official website of the Central Statistics Agency (BPS). The data analysis methods employed in this study are Confirmatory Factor Analysis (CFA) and multiple linear regression. The results indicate that economic growth, investment, and the Human Development Index (HDI) have a significant effect on labor absorption in Medan City.